Cellarium UiTM Shah Alam: a web-based management and tracking information system / Ahmad Zulkalnaim Mohd Nor - Mohd Nor, Ahmad Zulkalnaim (2020)
I am the people that was like buys something in online platform such as Shopee, Lazada and so on. The items that was buy are direct deliver to my house. While I live in collegue of UiTM Shah Alam, everythings change, the collegue not accept all of post to collegue but can deliver in the address which is knows a Cellarium Uitm Shah Alam. All of student can post their parcel to Cellarium. The existing system that Cellarium use is keeping the data of deliver items in Microsoft Excel and Google Drive. So now, the project should be develop to help the staff manage their deliver items and store the information using a Webbased system and ease the student to search their parcel things information. From the poject, students will able search all of information in the Web-based application.